(untitled) (Journal of the College of Education for Women, 2019)
The Caves within Surdash that are located in the northwest of Sulaymaniyah governorate in Iraq within the area (672) km district have been studied as they characterized by natural variable criteria reflected in turn on caves formation. One of the remarkable criteria is the characteristic of geological formations which include(12) Geological Formation, (6)of them Karst with high permeability. The field study showed that a high number of Caves in these karst formations in addition to the prevalence of geological formations with (75) linear structures extending NE-SW directions as well as the availability of water resources. Studies approved that caves vary in their sizes according to inverse relationship between caves areas and how close or far from sea level, thus, caves areas (square meters) were from (6-2176m2) within heights from (500-1600m) above sea level, also the study demonstrates that caves vary in their lengths from (4-1200m) besides doing the comprehensive study for geomorphologic and geological characteristics for caves and doing morphemic measurements of them. Thy study has concluded that uses of caves vary over time even for a single cave and now its uses vary as animal’s shelter, tourism, and religious or with no use.